Determining the rotation direction in pulsars - Renaud Gueroult (Nature Portfolio, 2019)
Interstellar magnetic fields determined from pulsar polarimetry in the GHz-band may be biased by mechanical-optical rotation in pulsars’ magnetospheres. Here the authors show how observations at sub-GHz frequencies can be used to resolve such a bias and determine pulsar rotation directions.